Tell Me a Story: Religion, Imagination, and Narrative Involvement - Black, Jessica E.; Oberstein-Allen, Molly; Barnes, Jennifer L. (Journal for the Cognitive Science of Religion, 2020)
Sacred stories and religious texts play a central role in religion, yetthere is a paucity of research investigating the relationship betweenreligiosity and individual differences in how people engage with stories.Here, we examine the relationship between religiosity, as well asa belief in God, and three variables related to how individuals interactwith narratives: a tendency to become absorbed in stories (transportability),a tendency to form relationships with the characters in stories(parasociability), and a reluctance to imaginatively engage withimmoral fictions (imaginative resistance). Although transportabilitywas only weakly related to intrinsic religiosity, both parasociability andimaginative resistance were correlated with a range of religiosity measures.Notably, the relationship between parasociability and religiositywas mediated by personal involvement with religious texts.